(untitled) (Research, Society and Development, 2021)
Introduction: The extraction of a dental element results in changes in bone architecture and remodeling of the underlying soft tissue. The immediate implantation came with the purpose, mainly, to preserve the alveolus walls; but, it may be associated with marginal recession. Personalized healers came to meet this demand; as it seals the implants and leads to individualized healing. The gingival contour of the implant is an area of ​​paramount importance with regard to aesthetic results and subsequent adaptation of dental crowns. Objective: Through a literature review, demonstrate the advantages, disadvantages and assistance of personalized healers in the gingival ridge healing process after implant surgery. Methodology: A bibliographic search will be carried out in Portuguese and English in Scielo, PubMed, Lilacs and Bireme using the following terms: personalized healing; implant dentistry; immediate implant. Full articles will be selected and included in this review. Expected results: Collaborate with an existing scientific discussion and understanding of the technique with personalized healing and its assistance in Implantology. Conclusion: The use of personalized healers optimizes the postoperative recovery process, helping to obtain a positive result in the rehabilitation treatment.